INVENTORY OF FOOD SOURCE PLANTS FOR HONEY BEES (APIS CERANA) IN BUANA SAKTI VILLAGE, BATANGHARI DISTRICT, EAST LAMPUNG REGENCY - Setiawan, Iwan; Susilawati, Endang (Sylva Jurnal Ilmu-ilmu Kehutanan, 2023)
AbstractOne sector of non-timber forest products (NTFPs) that is a favorite in the national and international markets is beekeeping. The main products from beekeeping are honey, royal jelly and bee pollen. The aim of this research is to determine the types of plant sources of food for honey bees, the density, frequency, importance index of each type of plant source of food for honey bees and the diversity of plant sources of food for honey bees based on their habitus in Buana Sakti Village. This research uses a centralized circle method which is placed systematically, with sample plots made in the form of a circle covering an area of 0.05 ha with a radius of 12.6 m, the sampling intensity used is 0.52%, so the observed sample area is 0.8 Ha. Based on the research results, it is known that there are 43 types of plants, 37 types of which are food sources for honey bees consisting of plantation plants, agricultural plants, ornamental plants, forestry plants and grass. The habitus of the 43 types of plants consists of 22 types of trees, 6 types of shrubs, 2 types of lianas and 13 types of herbs. Corn (Zea mays) is the type of plant that has the largest density, namely 225 individuals/ha, while the largest frequency value is owned by the plant species, Mimosa pudica, which is 0.563. The highest level of species control for the type of forestry plant that feeds honey bees (Apis cerana) is owned by mangium (Acacia mangium) with an INP of 15.302%. Meanwhile, for agricultural crops as a food source for honey bees, the highest level of species control is owned by corn with an INP of 17.686%.